2018
DOI: 10.1016/j.jdermsci.2018.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of topical SR-T100 gel in treating actinic keratosis in Taiwan: A Phase III randomized double-blind vehicle-controlled parallel trial

Abstract: The imitation of the study was that not all the treated AK lesions were confirmed by histopathology. The diagnostic uncertainty may contribute to the high partial clearance rate in the vehicle group since the clinical-diagnosed AK showed higher clearance rate compared to histopathology-confirmed AK. The use of occlusive dressing was another possible explanation for high placebo effects. The results suggested that topical SR-T100 gel may be an effective and safe treatment for field therapy of AK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…SR-T100, a newly patented product extracted from Solanum incanum, which contains solamargine alkaloid as the main active ingredient, is a potent inducer of apoptosis in different cancer cells that upregulates the expression of death receptor signaling cascades [42,43]; it downregulated Bcl-X L but upregulated Bax and caused caspase-3 activation of the mitochondrial pathway [44,45]. SR-T100 has been used as an anticancer drug for clinical therapy [46,47]. To elucidate the underlying mechanisms of chemoresistance affecting cell migration in ovarian cancer, several chemoresistant human ovarian cancer IGROV1 sublines to cisplatin or SR-T100 were established and applied in this study.…”
Section: Chemoresistant Igrov1 Sublines Exhibit Mesenchymal Morphologmentioning
confidence: 99%
“…SR-T100, a newly patented product extracted from Solanum incanum, which contains solamargine alkaloid as the main active ingredient, is a potent inducer of apoptosis in different cancer cells that upregulates the expression of death receptor signaling cascades [42,43]; it downregulated Bcl-X L but upregulated Bax and caused caspase-3 activation of the mitochondrial pathway [44,45]. SR-T100 has been used as an anticancer drug for clinical therapy [46,47]. To elucidate the underlying mechanisms of chemoresistance affecting cell migration in ovarian cancer, several chemoresistant human ovarian cancer IGROV1 sublines to cisplatin or SR-T100 were established and applied in this study.…”
Section: Chemoresistant Igrov1 Sublines Exhibit Mesenchymal Morphologmentioning
confidence: 99%
“…SR-T100 gel, not to be confused with the radiotherapy SRT-100, is a topical antiproliferative agent, with active ingredients solamargine, solasodine and solasonine, thought to treat AKs through modulation of the tumor necrosis factor receptor signaling pathway [84]. A study in Taiwan reported 32% complete clearance rate and 72% partial clearance rate for the group receiving SR-T100 gel compared with 12% complete clearance and 37% partial clearance rate for the control group [85]. The odds ratio for complete clearance was 2.14 and 4.36 for partial clearance [85].…”
Section: Management/treatmentmentioning
confidence: 99%
“…A study in Taiwan reported 32% complete clearance rate and 72% partial clearance rate for the group receiving SR-T100 gel compared with 12% complete clearance and 37% partial clearance rate for the control group [85]. The odds ratio for complete clearance was 2.14 and 4.36 for partial clearance [85]. The study gel was applied to an area that covered the AK and then covered by an occlusive dressing for eight hours daily for 16 weeks.…”
Section: Management/treatmentmentioning
confidence: 99%
“…At present, the treatment modalities of AK are divided into lesion‐targeted therapies and field‐directed therapies 13 . Recently, a traditional medicinal herb, topical SR‐T100 gel extracted from Solanum undatum (synonym: Solanum incanum ), was used to treat AK in a phase III trial 13 . The results demonstrated that SR‐T100 gel is an effective and safe treatment for field therapy of AK.…”
Section: Introductionmentioning
confidence: 99%